Contribution to the Synthesis, Characterization, Separation and Quantification of New N-Acyl Thiourea Derivatives with Antimicrobial and Antioxidant Potential - Roxana Roman; Lucia Pintilie; Diana Camelia Nuță; Miron Teodor Căproiu; Florea Dumitrașcu; Irina Zarafu; Petre Ioniță; Ioana Cristina Marinaș; Luminița Măruțescu; Eleonora Kapronczai; Simona Ardelean; Carmen Limban (MDPI AG, 2023)
The present study aimed to synthesize, characterize, and validate a separation and quantification method of new N-acyl thiourea derivatives (1a-1o), incorporating thiazole or pyridine nucleus in the same molecule and showing antimicrobial potential previously predicted in silico. The compounds have been physiochemically characterized by their melting points, IR, NMR and MS spectra. Among the tested compounds, 1a, 1g, 1h, and 1o were the most active against planktonic Staphylococcus aureus and Pseudomonas aeruginosa, as revealed by the minimal inhibitory concentration values, while 1e exhibited the best anti-biofilm activity against Escherichia coli (showing the lowest value of minimal inhibitory concentration of biofilm development). The total antioxidant activity (TAC) assessed by the DPPH method, evidenced the highest values for the compound 1i, followed by 1a. A routine quality control method for the separation of highly related compounds bearing a chlorine atom on the molecular backbone (1g, 1h, 1i, 1j, 1m, 1n) has been developed and validated by reversed-phase high-performance liquid chromatography (RP-HPLC), the results being satisfactory for all validation parameters recommended by the ICH guidelines (i.e., system suitability, specificity, the limits of detection and quantification, linearity, precision, accuracy and robustness) and recommending it for routine separation of these highly similar compounds.